Productivity aspects of driven pile operations in Singapore - Hor, Puey Sheng. (2008)
This study presents findings on pre-cast reinforced concrete driven pile productivity levels. Measurements were made for two case studies on pre-cast reinforced concrete piles utilising a performance indicator for bored piling recently developed by Lee & Mahmood. A comparison has been made between the productivity levels of these two driven piles case studies, namely a condominium and a commercial building. Factors influencing productivity performance of driven piles have been highlighted. A comparison has been made on the productivity levels of the above two piling systems, namely bored piling (after Lee & Mahmood) and driven piles used by the author. Productivity levels for the driven piles case studies are found to be consistently higher than the productivity levels for the projects using the bored pile system. Conclusions made indicated that a driven pre-cast reinforced pile system offers an economically viable alternative. Advantages and limitations of the productivity model for wider application have also been reviewed and presented. This study also proposes methods to raise and solve some of the issues affecting productivity problems in Singapore.